Antibacterial Effectiveness of Jatropha Leaf Extract (Jatropha curcas L.) against Aggregatibacter actinomycetemcomitans: In Vitro Study - Shieny Lokanata; Molek; Muthia Ayu Siregar (HM Publisher, 2023)
Background: Periodontal disease is one of the most common dental and oral health problems. Periodontal disease is characterized by inflammation as well as damage to the periodontal tissues, including the alveolar bone, cementum, gingiva, and the periodontal ligament. Aggregatibacter actinomycetemcomitans is the dominant bacterium in cases of periodontitis. Jatropha curcas plant is one of the ingredients that has been widely used for traditional medicine in the community, especially for the leaves. This plant is rich in active compounds such as alkaloids, tannins, phenols, flavonoids, and saponins, which are effective against gram-positive and gram-negative bacteria. This study aimed to determine the effectiveness of Jatropha extract (Jatropha curcas L.) as an antibacterial against Aggregatibacter actinomycetemcomitans in vitro. Methods: In vitro experimental studies. A total of 28 petri dishes contained bacterial colonies Aggregatibacter actinomycetemcomitans were used and divided into 7 test groups, treatment, and control groups. Obtained data were analyzed using SPSS program. Results: Jatropha extract treatment group with a concentration of 35% to 65% had optimal antibacterial abilities as the dose increased. This study also showed that at a concentration of 25%, Jatropha curcas extract did not have the antibacterial ability. Conclusion: Jatropha curcas extract has an antibacterial effect as the concentration of the extract increases againts Aggregatibacter actinomycetemcomitans.